A potential treatment option for transformed small-cell lung cancer on PD-L1 inhibitor-based combination therapy improved survival. (January 2023) - Zhang, Chan-Yuan; Sun, Hao; Su, Jun-Wei; Chen, Yu-Qing; Zhang, Shi-Ling; Zheng, Ming-Ying; Li, Yu-Fa; Huang, Jie; Zhang, Chao; Tai, Zai-Xian; Cai, Miao; Zhang, Xu-Chao; et al.
Highlights: The ORR of ABCP/ECT for T -SCLC exceeds 70 %, with a mPFS of 5.1 m. PD-L1 inhibitor-based combination therapy significantly prolonged pOS of T -SCLC. Combination immunotherapy could serve as a potential treatment option for T -SCLC. Upregulation of SFTPA1, EGFR L858R, or PD-L1 ≥ 1 % may benefit these patients. Abstract: Objectives: Transformed small-cell lung cancer ( T -SCLC) has an extremely poor prognosis, and no remedies based on immunotherapy have been evaluated among T -SCLC patients. We retrospectively analysed the efficacy and safety of combining atezolizumab with chemotherapy for T -SCLC. Methods: Forty-seven patients harbouring EGFR mutations who developed T -SCLC were enrolled. Eleven patients who used immunotherapy were defined as the I/O group, and the remaining 36 were defined as the Non-I/O group. Clinical characteristics, pathological data, and survival outcomes were collected. RNA sequencing and whole-exome sequencing (WES) were performed for in-depth analysis. Results: All patients received at least one line of EGFR-TKI before rebiopsy to confirm T -SCLC. Nine patients received atezolizumab-bevacizumab-carboplatin-paclitaxel (albumin-bound) (ABCP), and the remaining 2 received atezolizumab-etoposide-carboplatin (ECT) in the I/O group. The objective response rate was 73 % (8/11). The median progression-free survival (mPFS) of T -SCLC on post-transformation therapy with I/O group and Non-I/O group was 5.1 m and 4.1 m, respectively. The median post- T -SCLC overall survival of the I/O group was significantly longer than that Non-I/O group (20.2 m vs 7.9 m, P ＜ 0.01). T -SCLC harbouring EGFR L858R tended to be longer than EGFR 19del (mPFS: not reached vs 3.7 m, P = 0.11). Positive PD-L1 status was also associated with PFS benefits (mPFS: 6.0 m vs 3.7 m, P = 0.20). Furthermore, RNA sequencing revealed that expression of SFTPA1 is significantly higher in the durable clinical benefit group. WES showed that STC2 mutation is more frequently observed at the time-point immunotherapy acquired resistance. Combination therapy based on a PD-L1 inhibitor was well tolerated, and the safety profile was consistent with previously reported studies. Conclusion: Our study first demonstrated that a PD-L1 inhibitor combined with chemotherapy ± bevacizumab could be a potential safe option for specific SCLC-transformed patients. Subsequent studies with more patients are essential to verify the efficacy and potential biomarkers.